DEMOGRAPHIC VARIABLE CONNECTION WITH NURSE CARING BEHAVIOR IN HOSPITAL DR. DJASAMEN SARAGIH SIANTAR 2019 - Karo, Mestiana; Puji, Maria; Situmorang, Harta Florida (Jurnal Kesehatan Budi Luhur : Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2020)
Caring behaviour is a moral attitude in nursing practice. The caring nature of nurses when dealing with sick people and the patient's family every day must show empathy, sensitivity, and responsiveness to patient needs. This study aims to determine the relationship of demographic variables with the caring behaviour of nurses in Dr Djasamen Saragih Pematang Siantar in 2019. The study design used a descriptive correlation design with a cross-sectional approach. The sampling technique in this study used quota sampling with a sample size of 144 respondents. The instrument used was a demographic variable questionnaire sheet with nurses caring behaviour, where nurses caring behaviour questionnaire consisted of 5 themes. One Way Anova test results obtained age demographic variables p = 3.663, sex p = 2.859, on theme 2 obtained p = 0.036, religion p = 1.087, practice area p = 1.43, and on theme 3 known p = 0.014, education p = 3.003, term p = 3.008, length of service p = 3.174 (p <0.05). These results indicate in general there is no relationship between demographic variables with caring behaviour of nurses, but on the theme of 2 sexes and the theme of 3 practice areas, there is a relationship between demographic variables with caring behaviour of nurses in RSUD Dr Djasamen Saragih Pematang Siantar in 2019. This research is expected to be used as additional knowledge in the field of nursing.   Keywords : Demographic variables, Caring Behavior